A case study on the mobility and accessibility of wheelchair bound residents of two selected institutions based on universal design - Romero, Cherry Ann E.
This is a case study of the mobility and accessibility of the wheelchair bound residents of two selected institutions that house the physically disabled namely, Tahanang Walang Hagdanan and Bahay Mapagmahal 1. Data were gathered through interviews, observations, a survey, and documentations of different measurements of design elements, floor plans and photos. They were evaluated according to the parameters set by Universal design. The findings and results of the data gathered have proven that the Housing Unit of Tahanang Walang Hagdanan has complied with almost all of the mobility and accessibility inside the building. On the other hand, in Bahay Mapagmahal 1, many aspects of design based on Universal design were not applied in the institution. However, the residents were satisfied with their mobility and accessibility inside the building. The results of the survey may have been affected by the respondents' culture and personal sentiments about the institution. The budget and size of the spaces provided for the institutions, especially in Bahay Mapagmahal 1, were found to be limiting factors in designing for wheelchair bound persons. The researcher concluded that not all of the parameters set by the Universal design were applied in the two selected institutions but the residents were found to be satisfied with them.